Coherent imaging of biological samples with femtosecond pulses at the free-electron laser FLASH - Mancuso, Adrian; Gorniak, Thomas; Staier, Florian; Yefanov, O. M.; Barth, Ruth; Christophis, Christof; Reime, B.; Gulden, J.; Singer, A.; Pettit, M. E.; Nisius, Th; Wilhein, Th; et al. (New journal of physics, 2010)
Coherent x-ray imaging represents a new window to imaging non-crystalline, biological specimens at unprecedented resolutions. The advent of free-electron lasers (FEL) allows extremely high flux densities to be delivered to a specimen resulting in stronger scattered signal from these samples to be measured. In the best case scenario, the diffraction pattern is measured before the sample is destroyed by these intense pulses, as the processes involved in radiation damage may be substantially slower than the pulse duration. In this case, the scattered signal can be interpreted and reconstructed to yield a faithful image of the sample at a resolution beyond the conventional radiation damage limit. We employ coherent x-ray diffraction imaging (CXDI) using the free-electron LASer in Hamburg (FLASH) in a non-destructive regime to compare images of a biological sample reconstructed using different, single, femtosecond pulses of FEL radiation. Furthermore, for the first time, we demonstrate CXDI, in-line holography and Fourier transform holography (FTH) of the same unicellular marine organism using an FEL and present diffraction data collected using the third harmonic of FLASH, reaching into the water window. We provide quantitative results for the resolution of the CXDI images as a function of pulse intensity, and compare this with the resolutions achieved with in-line holography and FTH.
Gesehen am 03.05.2023